True and Fair View of Key Performance Indicators in Evaluating Companies’ Compliance with the EU Green Taxonomy Regulation - Skoczylas, Wanda; Mućko, Przemysław; Kintop, Gabriela (Prawdziwy i rzetelny obraz kluczowych wskaźników wyników w ocenie zgodności przedsiębiorstw z unijnym rozporządzeniem w sprawie zielonej taksonomii, 2024)
Aim: Identify the problems and challenges faced by accounting in the process of legitimising orga-nizations with financial mandatory key performance indicators that are designed to measure the share of the company’s environmentally sustainable activities. Methodology: Literature review, regulatory analysis, desk research. Findings: The study identified the problems and challenges in the reporting of KPIs for three elements, namely revenue, CapEx, OpEx of environmentally sustainable activities. These problems arose from an analysis of the basic qualitative characteristics of information: its representational faithfulness, completeness, neutrality and accuracy. Implications: Provide a discussion base point for business practice in the area of sustainability reporting to mandatory financial KPIs, meeting the aims and objectives of the regulation. Originality/value: The article contributes and fills the existing gap in the literature on the true and fair view of environmentally sustainable economic activity in line with green taxonomy. The results may provide inspiration for future research.
Financial Sciences. Nauki o Finansach, 2024, vol. 29, no. 2, s. 51-59
Keywords: EU Green Taxonomy; sustainability reporting; true and fair view; accounting; key performance indicator; zielona taksonomia UE; prawdziwy i rzetelny obraz; rachunkowość; kluczowe wskaźniki efektywności